The Reasons for the Weakness of Public School Students in English Language in the State of Kuwait from the Perspective of School Principals and their Assistants - Alkhrisha, Mallouh; Al-Mutairi, Hussein (Dirasat: Educational Sciences, 2022)
Objectives: The study aims at identifying the reasons of public schools students’ weakness in English language in the State of Kuwait. The population of the study consisted of all schools’ principals and their assistants in Aljahra Governorate for 2019/2020 school year. The sample of the study consisted of (284) principals and assistants who were selected using a stratified random sampling procedure . Methods: To achieve the objectives of the study, a descriptive analytical approach was utilized. The researchers developed a questionnaire composed of (30) items and divided into three dimensions: student, teacher, and curriculum. Results: The results of the study revealed that the degree of reasons for the weakness of students in public schools in the English language in the State of Kuwait was moderate. Moreover, the results revealed that there were statistically significant differences in the responses of school principals and their assistants about the reasons related to the three dimensions due to qualification in favor of graduate studies, and due to experience in favor of those with more experience. Conclusions: The study stresses the necessity of encouraging teachers to diversify their teaching methods and focusing on the applied side of the language. Furthermore, it recommends designing English language curricula in a way that they are more relative to the students’ backgrounds and culture.